Constraints to speciation despite divergence in an old haplochromine cichlid lineage. (7th January 2023) - Müller, Claudio; Moser, Florian N; Frei, David; Seehausen, Ole
Abstract: Most of the 500+ cichlid species of Lake Victoria evolved very rapidly in the wake of an adaptive radiation within the last 15, 000 years. All 500 species have evolved from just one out of five old cichlid lineages that colonized the lake. Endemic to the Lake Victoria region, Astatoreochromis alluaudi is a member of an old haplochromine lineage that never speciated in the region. Even though the species occurs in a wide range of habitats, there were no indications of evolutionary diversification. Here, we tested predictions of several hypothetical mechanisms that might constrain speciation, including high dispersal rates, a generalist life style and the lack of behavioral assortative mating. Genomic analyses of individuals from 13 populations revealed several genomically distinct groups, associated with major habitat classes, indicating the existence of two distinct ecotypes. We found significant phenotypic differences between these ecotypes in the wild, which were retained under common-garden conditions, potentially indicating heritable phenotypic adaptations. Female mate choice experiments revealed the absence of behavioral assortative mating despite genetic and phenotypic differentiation between ecotypes. We suggest that the lack of coupling between behavioral mating preferences and phenotypic and genetic divergence constrains speciation in this cichlid.